The Development of UTHM Course Recommender System For SPM Graduates - Mohd Norrahim, Nurul Arifah; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2022)
UTHM Course Recommender System for SPM Graduates (UCRS) is a web-based system that help students find suitable diploma courses in University Tun Hussein Onn Malaysia (UTHM) based on their SPM results and personality test since most of SPM Graduates are not clear with their future, less knowledge on choosing right courses and no appropriate system to validate their choices. This UCRS will be design, developed and be tested to produce a good system to be use by SPM Graduates and being monitored by an admin which is UTHM staff. Next, theory and technique being applied in UCRS system are Rule-Based Technique to determine courses based on SPM Result and J. Holland Theory used to determine personality type of students to find suitable courses for them. By using Iterative model as the method to conduct this system, five phases need to be done thoroughly which is, planning and requirement, analysis and design, implementation, testing and evaluation. Besides that, PHP language as the programming language and Visual Studio Code is the programming tool with MySQL as the database to build up UCRS system. As a result, a system will be able to give suggestions to SPM Graduates about their chosen courses and can determine their courses by SPM Result or personality Test.